Love's healing path [large type] - Williams, Lacy (Williams, Lacy. Wagon train matches, 2025)
"Maddie Fairfax may be young, but on this Oregon-bound wagon train, the pioneers welcome help from the self-trained nurse. Until Dr. Jason Goodwin joins up with their company. The doctor portrays a frosty exterior, but Maddie may be the only one who sees the profound loneliness that haunts him. After losing his wife and children in a terrible accident, Jason has vowed not to open his heart again. But when Maddie takes on the care of three young orphans, Jason finds himself entangled in the lives of the makeshift family. And as their journey west continues, Maddie's radiant compassion begins to light up the darkest corners of his heart. Until the unthinkable happens. Will Jason's guarded heart and Maddie's untamed spirit pull them apart?"--